1996
DOI: 10.1002/jmri.1880060602
|View full text |Cite
|
Sign up to set email alerts
|

MR lesion detection in a breast cancer population

Abstract: Implementation of MR imaging of the breast as an extension of the existing imaging modalities in the diagnosis of breast cancer was evaluated in a university cancer center, MR imaging of the breast was performed in 54 patients, in whom the MR results were compared with the triple test (the combination of clinical examination, mammographic evaluation, and cytology) and the final histological diagnosis. MR imaging of the breast depicted 30 of the 33 malignancies (sensitivity, 91%). In two of the malignancies, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…This was also discussed by O bdeijn et al. (15) in their evaluation of mammography, clinical examination and ultrasonography compared to MR in 54 patients, where their findings were in accordance with our present results. They found MR to be false‐negative in 3 patients with in situ cancers and false‐positive in 7 patients with scar tissue, mastitis and proliferative dysplasia.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This was also discussed by O bdeijn et al. (15) in their evaluation of mammography, clinical examination and ultrasonography compared to MR in 54 patients, where their findings were in accordance with our present results. They found MR to be false‐negative in 3 patients with in situ cancers and false‐positive in 7 patients with scar tissue, mastitis and proliferative dysplasia.…”
Section: Discussionsupporting
confidence: 94%
“…In recent years MR imaging of the breast has proven to be valuable in certain applications (2, 5, 7, 10, 12, 14). Previous studies have shown MR to be useful as an adjunct to TD in patients with dense parenchyma (15) and for providing the highest possible sensitivity and negative predictive value (13). There have been comparisons of MR to TD for assessing local recurrence (11) and for preoperative detection of multifocal or multicentric breast tumours (3).…”
mentioning
confidence: 99%
“…Without the use of contrast agent, MRI is of very little value to detect breast cancers. Currently, CE MRI of the breast is known to be the most sensitive modality to detect invasive breast cancer, yielding sensitivities approaching 100% [33][34][35][36]. Sensitivity is not impaired by dense parenchyma.…”
Section: Ce Mri Of Symptomatic Womenmentioning
confidence: 99%
“…In those studies the breast cancers that were missed were DCIS (43, 44). Obdeijn et al (46) reported a 91% detection rate for palpable lesions. Small breast cancers (less than 1 centimeter) can now be detected by MRI (47, 48).…”
Section: Present Role Of Mrimentioning
confidence: 99%